Determination of chlorothalonil and its metabolite 4-hydroxychlorothalonil residues in animal-derived food by ultra-high performance liquid chromatography-tandem mass spectrometry - LIU Xiaofang; LI Zheng; HE Hao; JIANG Junjie; CHEN Yuanyuan (Shipin yu jixie)
ObjectiveTo establish a method for simultaneous determination of chlorothalonil and its metabolite 4-hydroxychlorothalonil residues in animal-derived food by ultra-high performance liquid chromatography-tandem mass spectrometry.MethodsThe samples were extracted by oscillating with acetonitrile solution of 1% acetic acid, defatted with n-hexane, purified by matrix dispersible solid phase extractant (PSA, anhydrous magnesium sulfate), separated by Waters BEH C18 column under a gradient elution program using 0.1% formic acid aqueous solution and acetonitrile as the mobile phases. The anion multiple reaction monitoring model (MRM) of atmospheric pressure chemical ionization source (APCI) was used for the determination, and the matrix matching external standard method was used for quantitative determination.ResultsThe linear relationships of chlorothalonil and 4-hydroxychlorothalonil were good in the range of 5~500 μg/L, and the limits of quantitation were 0.005 mg/kg. The average recoveries of chlorothalonil and 4-hydroxychlorothalonil were 69.3%~111.0% and 65.3%~117.9%, respectively. The relative standard deviations of chlorothalonil and 4-hydroxychlorothalonil were 1.6%~10.8% and 1.1%~9.0%, respectively.ConclusionThe method is simple, rapid, sensitive, accurate and reliable for simultaneous determination of chlorothalonil and its metabolite 4-hydroxychlorothalonil in animal-derived food.